Study on the Effect of Fusarium oxysporum and Macrophomina phaseolina on the Proximate Composition of Jatropha curcas Seed - Isalar, O. F.; Ataga , A. E. (Innovations in Microbiology and Biotechnology Vol. 3, 2022)
A study was carried out on the effects of Fusarium oxysporum and Macrophomina phaseolina on the proximate compositions of Jatropha curcas seeds. Jatropha curcas is a plant with high potential source of biodiesel production. The proximate composition of the various nutrient component (Dry matter, Moisture, Lipids, Free fatty Acid, Carbohydrates, Ash, Fibre, Crude protein and Amino acid) in both fungus-inoculated and uninoculated seeds at the incubation period of 7days were measured by the methodology proposed by [1]. The oil content and fatty acid (FA) composition of J. curcas seeds are of vital importance. The results obtained from each food component were subjected to statistical analysis using the Analysis of Variance (ANOVA). In the results of the proximate analysis, Fusarium oxysporum and Macrophomina phaseolina caused significant increase (P=0.05) in moisture content 7.0% and 6.0%, crude protein 2.1% and 1.7%, and 0.2% and 0.7% ash, respectively in seeds inoculated at room temperature (28±2oC) for 7days when compared with uninoculated controls. There was a remarkable reduction of 11% and 10.5% in dry matter, 0.8% and 0.2% in carbohydrate, 5.0% and 3.3% in lipids, 2.6% and 5.7% in fibre content of the seeds inoculated with Fusarium oxysporum and Macrophomina phaseolina, respectively when compared with their controls. The results are discussed in relation to the changes in the nutritional composition of the seeds due to the activities of these pathogenic fungi.